Case Report: Endovascular Treatment of a Giant Distal PICA Aneurysm in Association With a Cerebellar AVM: A Report on Treatment Considerations and a Literature Review - Khayat, Hassan A.; Hawkes, Christine M.; Algird, Almunder R. (Frontiers in Neurology, 2020)
Abstract: Background: Distal posterior inferior cerebellar artery (PICA) aneurysms are uncommon intracranial vascular lesions. The coincidence of these aneurysms and Arteriovenous malformation (AVM) is even more rare. Since 1956, a total of 57 cases of distal PICA aneurysms associated with AVM have been reported with a clear and adequate description. None of these reports describe a giant prenidal aneurysm at this particular location. The paucity of natural history data as well as lack of consensus about treatment strategies in such cases presents a significant challenge that requires an individualized management approach. Case description: A 68-year-old male presented with recurrent episodes of nausea and vomiting precipitated by physical exertion and change of head position. An MRI brain demonstrated a giant partially thrombosed right posterior inferior cerebellar artery (PICA) aneurysm with a mass effect on the floor of the fourth ventricle. A conventional cerebral angiogram revealed a giant (3.1 x 3.1 x 2.8cm) distal right PICA pre-nidal aneurysm with two smaller distal PICA aneurysms. An AVM (Spetzler-Martin Grade 1) supplied by the right PICA, as well as the right superior cerebellar artery (SCA) was also identified on cerebral angiography (not seen on MRI). Endovascular coil embolization with parent vessel sacrifice was performed to occlude the giant aneurysm. Due to the asymptomatic nature, low risk of rupture, and the patient’s age, AVM treatment was deferred. Conclusion: For PICA aneurysm-AVM complexes, meticulous evaluation of the morphology, associated anatomy and comparative risk analysis for both lesions are key for treatment planning. Distal PICA aneurysms can be treated safely with parent vessel occlusion, particularly in the case of prenidal aneurysms.